THE STATE AS A SUBJECT OF FORMATION OF THE NATIONAL STARTUP ECOSYSTEM - Sytnik, N. (Scientific Bulletin of Kherson State University. Series Economic Sciences, 2020)
The realization of Ukraine's innovation potential is permanently hampered by a number of political and socio-economic factors. However, despite numerous problems in the economy, innovative entrepreneurship in the form of startup projects shows stable growth. The Ukrainian startup sector has become one of the few sectors of the economy that has been developing dynamically in recent years. International experience indicates that the state is an important player in building the national startup ecosystem. In particular, the state plays a leading role in preventing the outflow of startups to other world ecosystems. The purpose of the article was to establish the features of the state support for the national startup ecosystem and outline the ways to strengthen this support. Based on the analysis of international experience, the existing approaches, methods, and tools used in the world practice to support the startup ecosystems were identified. In terms of the development of the startup ecosystems, two major types of state policies are outlined: proactive policy and reactive policy. The paper provides key characteristics of theses types of policies. The analysis of government support for national startup ecosystem was conducted. Although the development of innovative entrepreneurship was defined as a strategic priority of Ukrainian government, the speed of implementation of practical measures aimed at achieving this goal is insufficient. Positive tendencies in the state support of Ukrainian startups as well as the main directions for state stimulation of the domestic startup ecosystem were highlighted.To stimulate the development of the domestic startup ecosystem, the following areas of state support were considered: legal regula-tion, startup investment, human capital development, competence centers, infrastructure development, media and event management. The factors that inhibit state support for startups were identified. In addition, the role of the private sector in building the national ecosys-tem of startups was outlined. Promising area of further research is the analysis of trends in the global startup industry and comprehension of international experience to elaborate efficient tools for domestic startup ecosystem support. Keywords: startup, startup ecosystem, state policy, investments in startups, human capital, startup ecosystem infrastructure. У статті розглядається роль держави як суб’єкта формування вітчизняної екосистеми стартапів. На основі аналізу міжнарод-ного досвіду визначені існуючі у світовій практиці підходи до формування державної політики підтримки екосистеми стартапів, напрями та практичні інструменти стимулювання стартапів. Висвітлені відмінності між проактивною та реактивною політикою стимулюванння екосистеми стартапів. Проаналізовано сучасний стан державної підтримки стартапів в Україні. Хоча в Україні розвиток інноваційного підприємництва визначений як стратегічний пріоритет державної політики, однак темпи імплементації практичних заходів, спрямованих на досягнення цієї мети, є недостатніми. Визначені інструменти державного стимулювання вітчизняної екосистеми стартапів, що відносяться до державно-правового регулювання, інвестування стартапів, розвитку людського капіталу, створенння центрів компетенцій, інфраструктурного забезпечення, медіа та івент менеджменту. Ключові слова: стартап, екосистема стартапів, політика підтримки стартапів, інвестування стартапів, людський капітал, інфраструктура стартапів.